Exploring for New Insights in the Performance of a 3D Orbital Angular Momentum Mode-Sorter - Lightman, Shlomi; Wengrowitcz, Jonathan M.; Teitelboim, Ayelet; Gvishi, Raz; Hurvitz, Gilad (Frontiers in Physics, 2022)
Optical vortex beams are light beams that can carry orbital angular momentum (OAM). Hence, such beams may serve as potential candidates for carriers of information in optical communication and quantum optics applications. This is, owing to their spatial orthogonality, as these beams can be combined (multiplex) or separated (demultiplexed). We recently demonstrated a new method to detect OAM states by using 3D-direct laser printing fabrication process [1]. Measuring the mode-sorter performance was challenging, mainly due to mechanical and optical sensitivities originated from misalignments. In this work, this sensitivity was thoroughly examined. Pure OAM states having lateral and angular misalignments relatively to the mode-sorter were introduced, and cross talk between resolved states was theoretically simulated. The system is relatively vulnerable to small misalignments, which challenge its implementations in free-space communication systems. However, this might be an advantage for counseled communication, in which eavesdropping becomes more challenging, due to the angle-dependent increased modal cross talk.